Low-temperature dipolar polarization mechanisms in Ba0·9La0·1Fe12O19 ceramic hexaferrite. Issue 15 (15th October 2020) - Guerrero, F.; Govea-Alcaide, E.; Mariño-Castellanos, P.; Romaguera-Barcelay, Y.; Anglada, J.; Leyet, Y.; Almeida, A.; Vilarinho, R.; Agostinho-Moreira, J.
Abstract: The complex eletrical permittivity and the thermally stimulated depolarization current responses of the M-type Ba0·9 La0·1 Fe12 O19 ceramic hexaferrite was investigated in the 10–300 K temperature range. The sample was obtained by using the conventional solid-state reaction method. From X-ray diffraction patterns we have found, by using the Rietveld refinement method, that most of the indexed reflections belong to BaM hexaferrite with spatial group P 63 m c (186), and less than 5% of α-Fe2 O3 secondary phase. It was found from magnetization measurements at room temperature values of saturation magnetization, remnant magnetization, and coercivity of 61.69 emu/g, 27.13 emu/g, and 1.71 kOe, respectively. Measurements of the real, ε ', and imaginary, ε ' ', parts of the complex electric permittivity, revealed two different polarization processes: a dipolar polarization process, characterized by a relaxation peaks of ε ' ' dependence, in the temperature range 50–130 K and the interfacial polarization in the temperature interval 150–300 K. The analysis of all experimental data suggested that dipolar polarization at low-temperature can be related to the off-equatorial displacement of the Fe 3+ at 2b and 6c sites, respectively. In association with the dipolar polarization process, a ferroelectric behavior between 10 and 80 K, was detected by using measurements of depolarization current as a function of temperature and at zero applied magnetic field.